Bioenergy from Microalgae – Vision or Reality?1. Issue 4 (28th May 2018) - Hoyer, Jan; Cotta, Fritz; Diete, Anja; Großmann, Jochen
Abstract: Microalgae are often heralded as a miracle cure to solve future questions concerning energy and food supply of the world's population. This is due to their vastly superior area productivity compared to terrestrial plants and the feasibility of cultivating them independently of arable land and fresh water. Algal biomass can be used as food and feed as well as a source for a plethora of biofuels and high value products such as nutraceuticals and pharmaceuticals. This review article seeks to shed light on recent advances in microalgal technology and their potential for the production of biofuels. Abstract : Being independent of drinking water and arable land, microalgae have the potential to serve as food and energy suppliers of the future. This review article gives an overview on recent developments in microalgae biotechnology and discusses its potential for the production of biofuels such as biogas and biodiesel.